2000
DOI: 10.1016/s0006-3495(00)76616-1
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Ion Permeation Through a Potassium Channel: Molecular Dynamics of KcsA in a Phospholipid Bilayer

Abstract: Potassium channels enable K(+) ions to move passively across biological membranes. Multiple nanosecond-duration molecular dynamics simulations (total simulation time 5 ns) of a bacterial potassium channel (KcsA) embedded in a phospholipid bilayer reveal motions of ions, water, and protein. Comparison of simulations with and without K(+) ions indicate that the absence of ions destabilizes the structure of the selectivity filter. Within the selectivity filter, K(+) ions interact with the backbone (carbonyl) oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
214
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(234 citation statements)
references
References 58 publications
18
214
2
Order By: Relevance
“…Similar coupled translocation has been observed in other simulations. 39,40 C. Coupling of carbonyl groups with water and K + Previous MD simulations studies 39,40 have shown that during the motions of the ions subtle changes in the backbone conformation of the selectivity filter can appear, which indicates towards a coupling between ion permeation and positional changes of the carbonyl groups. Similar findings can be reported from our simulations.…”
Section: B Dynamics Of K + and Water In The Selectivity Filtermentioning
confidence: 99%
“…Similar coupled translocation has been observed in other simulations. 39,40 C. Coupling of carbonyl groups with water and K + Previous MD simulations studies 39,40 have shown that during the motions of the ions subtle changes in the backbone conformation of the selectivity filter can appear, which indicates towards a coupling between ion permeation and positional changes of the carbonyl groups. Similar findings can be reported from our simulations.…”
Section: B Dynamics Of K + and Water In The Selectivity Filtermentioning
confidence: 99%
“…The availability of high-resolution crystallographic structures (2)(3)(4), together with the development of sophisticated computer models (5)(6)(7)(8)(9)(10), is providing us with a unique opportunity to refine our understanding of these systems at an unprecedented level. Although the complexity of these channels does present a formidable challenge to biomolecular modeling, it is particularly encouraging to note that many of the recent results from molecular dynamics (MD) simulations based on realistic all-atom models have been consistent with the information emerging from higher-resolution structural data (for a recent review, see ref.…”
mentioning
confidence: 99%
“…At the present time, this cannot be done by using simple ''brute-force'' MD simulations (11). According to single-channel measurements, the ionic flux across the KcsA under a transmembrane potential of 100 mV corresponds to the net translocation of approximately one ion in 10-20 ns (14), which is on the order of a typical MD trajectory (6)(7)(8)(9)(10). Despite the steady increase in computer power, the direct simulation of ionic fluxes across a selective biological channel with all-atom MD remains computationally prohibitive.…”
mentioning
confidence: 99%
“…Transport processes for membrane proteins are somewhat accessible within the time-scale limitations of all-atom simulations, and MD has had much success in analyzing these, for example, in K channels (27,28) and aquaporins (29)(30)(31), where the mechanism was first shown in a homology model (30). Previous studies of the LBD in MD have yielded valuable information about its function (32,33).…”
mentioning
confidence: 99%